2021
DOI: 10.3389/fcell.2021.657591
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Life Stress on the Brain and Behaviour: Insights From Zebrafish Models

Abstract: The early life period represents a window of increased vulnerability to stress, during which exposure can lead to long-lasting effects on brain structure and function. This stress-induced developmental programming may contribute to the behavioural changes observed in mental illness. In recent decades, rodent studies have significantly advanced our understanding of how early life stress (ELS) affects brain development and behaviour. These studies reveal that ELS has long-term consequences on the brain such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 234 publications
(347 reference statements)
0
17
0
Order By: Relevance
“…However, we observed significant upregulation of developmental processes and nervous system development in this treatment. Previous studies indicated that early life stress may have large effects on the developing brain and nervous system in vertebrates [ 33 , 34 ]. Further studies are needed to understand if exposure to genotoxicants after neurulation may affect sturgeons later in life and subsequently induce adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed significant upregulation of developmental processes and nervous system development in this treatment. Previous studies indicated that early life stress may have large effects on the developing brain and nervous system in vertebrates [ 33 , 34 ]. Further studies are needed to understand if exposure to genotoxicants after neurulation may affect sturgeons later in life and subsequently induce adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tran et al [ 61 ] suggest that chronic ethanol exposure in adult zebrafish attenuates dopamine, serotonin and associated metabolite reactions to secondary ethanol exposure. Similarly, developmental exposure to ethanol has been linked to shifts in baseline serotonin and dopamine [ 62 , 63 ], which in turn can influence social behaviour in zebrafish [ 64 ] and reduce their motivation to socialize [ 65 ]. It is therefore plausible that permanent shifts in baseline dopamine and serotonin resulting from ethanol exposure could persist in the next generation and influence some of the patterns observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Both the Sigmar1 tm1Lmon mouse line developed by Esteve [44] and the Sigmar1 Gt(IRESBetageo)33Lex line developed by Lexicon [54,55] did not show developmental defects and reproduced normally. The availability of a S1R KO zebrafish line will be of major use for future research, particularly since: (i) zebrafish embryos are nearly transparent which allows easy examination of the development of internal structures; (ii) the model is particularly prone to in vivo imaging and electrophysiological approaches; and (iii) eggs are fertilized and developed outside the mother's body, which makes zebrafish an ideal model organism for studying early development [56]. Indeed, S1R may play a major yet underexplored role during early development of many organs, including the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The behavioral analyses of the s1r +25/+25 larvae first revealed a hyperlocomotor response in the VMR test that appeared likely unrelated to visual or other neurosensorial modification. This phenotype trait is not shared by S1R KO mouse lines, since WT or KO mice failed to show basal hyperlocomotion compared to WT littermates, particularly when tested from 8 to 48-weeks of age and in different open-field or maze tests [44,55,56,60]. Locomotor behaviors, including walking in mice or swimming in zebrafish, are generated by networks of neurons known as central pattern generators located in the spinal cord of vertebrates.…”
Section: Discussionmentioning
confidence: 99%